The relation of drawing to education - Dial, Lillie Christena (My University, 1895)
Introduction: Drawing may be considered as one of the highest and most useful branch of study in the development of education. When we consider its relations to other arts we no doubt will place it at the head of them all, for it often aids in their production. In fact it is a lesson which constitutes nearly all experience of the action of man, and it is looked upon as an element of education, and the basis of all constructive arts.
Citation: Dial, Lillie Christena. The relation of drawing to education. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Drawing; Education; Art; Theses; Manuscripts (documents)